An Apoptosis‐Inducing Peptidic Heptad That Efficiently Clusters Death Receptor 5. Issue 16 (15th March 2016) - Valldorf, Bernhard; Fittler, Heiko; Deweid, Lukas; Ebenig, Aileen; Dickgiesser, Stephan; Sellmann, Carolin; Becker, Janine; Zielonka, Stefan; Empting, Martin; Avrutina, Olga; Kolmar, Harald
Abstract: Multivalent ligands of death receptors hold particular promise as tumor cell‐specific therapeutic agents because they induce an apoptotic cascade in cancerous cells. Herein, we present a modular approach to generate death receptor 5 (DR5) binding constructs comprising multiple copies of DR5 targeting peptide (DR5TP) covalently bound to biomolecular scaffolds of peptidic nature. This strategy allows for efficient oligomerization of synthetic DR5TP‐derived peptides in different spatial orientations using a set of enzyme‐promoted conjugations or recombinant production. Heptameric constructs based on a short (60–75 residues) scaffold of a C ‐terminal oligomerization domain of human C4b binding protein showed remarkable proapoptotic activity (EC50 =3 nm ) when DR5TP was ligated to its carboxy terminus. Our data support the notion that inter‐ligand distance, relative spatial orientation and copy number of receptor‐binding modules are key prerequisites for receptor activation and cell killing. Abstract : A modular approach to generate death receptor 5 (DR5) binding constructs comprising multiple copies of DR5 targeting peptide (DR5TP) covalently bound to biomolecular scaffolds of peptidic nature is presented. Multivalent ligands are obtained that specifically induce an apoptotic cascade in cancer cells. The number and spatial orientation of the copies are decisive for their receptor activation ability.